2014
DOI: 10.1186/1749-8090-9-125
|View full text |Cite
|
Sign up to set email alerts
|

Anaesthetic management of cytoreductive surgery followed by hyperthermic intrathoracic chemotherapy perfusion

Abstract: BackgroundMacroscopic cytoreductive surgery and hyperthermic intrathoracic chemotherapy perfusion (HITHOC) is a new multimodal approach for selected patients with primary and secondary pleural tumors, which may provide the patient with better local tumor control and increased overall survival rate.MethodsWe present a single-center study including 20 patients undergoing cytoreductive surgery and HITHOC between September 2008 and April 2013 at the University Medical Center Regensburg, Germany. Objective of the s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 40 publications
0
30
1
Order By: Relevance
“…As shown in Tables 1 and 2, total 5 articles were included in the meta-analysis (quantitative synthesis) [59] and 22 articles were included in the systematic review (qualitative synthesis). Among the 27 articles for systematic review and meta-analysis, 4 articles were from Japan, [5,6,10,11] 4 articles from China, [7,9,12,13] 4 articles from Italy, [1417] 4 articles from Netherlands, [1821] 3 articles from USA, [2224] 3 articles from Germany, [2527] 2 articles from Israel, [28,29] 1 from Turkey, [8] 1 from Australia, [30] and 1 from Korea. [31] The earliest was reported in 1995 by Matsuzaki et al from Japan (Matsuzaki, 1995], and the latest, up to May 2016, was from China by Liu et al [13] and from Italy by Ambrogi et al [17] …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in Tables 1 and 2, total 5 articles were included in the meta-analysis (quantitative synthesis) [59] and 22 articles were included in the systematic review (qualitative synthesis). Among the 27 articles for systematic review and meta-analysis, 4 articles were from Japan, [5,6,10,11] 4 articles from China, [7,9,12,13] 4 articles from Italy, [1417] 4 articles from Netherlands, [1821] 3 articles from USA, [2224] 3 articles from Germany, [2527] 2 articles from Israel, [28,29] 1 from Turkey, [8] 1 from Australia, [30] and 1 from Korea. [31] The earliest was reported in 1995 by Matsuzaki et al from Japan (Matsuzaki, 1995], and the latest, up to May 2016, was from China by Liu et al [13] and from Italy by Ambrogi et al [17] …”
Section: Resultsmentioning
confidence: 99%
“…[23] They also observed a persistently high concentration of intrapleural drugs as compared to plasma concentrations when the patients were given HITHOC. [22] Similarly, Ried and coworkers [27] from Italy reported that the mean area under curves (AUCs) of cisplatin in the perfusate were approximately 55 to 58 times greater than detected in the serum, and found that elevation of the cisplatin dosage to 150 mg/m 2 did not lead to a significant increase of the systemic cisplatin concentration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this setting, the surgical stress for the patient could J Thorac Dis 2018;10(Suppl 2):S228-S236 jtd.amegroups.com [9][10][11][12][13] 9 [7][8][9][10][11][12] 11 [7][8][9][10][11][12][13][14][15] 15 [9][10][11][12][13][14][15][16][17] 13 [8][9][10][11][12][13][14][15] 11 [7- be detrimental when associated with HITHOC. For this reason it is mandatory an appropriate anaesthetic protocol associated with advanced clinical monitoring to guide and improve intraoperative and postoperative patient's management.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, in a review about hyperthermic intra-peritoneal chemotherapy (HIPEC), Newton et al reported a complication rate major than 40%. The study highlights that the most common perioperative complications were respiratory and cardiovascular as well an early unset of kidney failure (11,12). Some authors showed that the intraoperative fluid management played a key role in the onset of postoperative complications after HIPEC (13).…”
Section: Introductionmentioning
confidence: 99%